Incidence of educational mismatch and earning in Pakistan - Muhammad Zaheer Khan; Said, Rusmawati; Mazlan, Nur Syazwani; Mohamed Nor, Norashidah (Public Library of Science, 2022)
This study empirically examines the incidence and earning effect of educational mismatch in the labor market of Pakistan. Microdata obtained from the labor force survey for the years (2013–14, 2014–15, 2017–18) is used for the analysis. The realized match approach is used to measure the required level of education, and the augmented mincerian model is used to determine the potential earning effects associated with the educational mismatch. The study found a considerable incidence of under-education and over-education in the labor market. Results show a positive return to under-education and over-education. However, the return to the required level of education is significantly higher than both the under-education and over-education.